2005
DOI: 10.1080/02844310410004964
|View full text |Cite
|
Sign up to set email alerts
|

The sural artery perforator flap for coverage of defects of the knee and tibia

Abstract: We reconstructed four knee and lower leg defects using the sural artery perforator flap between 2000 and 2003, and describe them here. The sural artery perforator flap can save the gastrocnemius muscle, its motor nerve, deep fascia, lesser saphenous vein, and sural nerve with no functional loss. Intramuscular dissection of the perforator achieves increased length of the pedicle compared with a conventional gastrocnemius myocutaneous flap. The flap is thin, and either the medial or lateral sural artery may be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 5 publications
1
19
0
Order By: Relevance
“…Taylor & Daniel 1 first suggested the medial sural vessels as the basis of a new flap donor site in 1975 and, two decades later, Montegut 2 presented the first clinical cases of the medial sural artery perforator flap. Subsequently, Cavadas 3 and other authors [4][5][6][7][8][9][10][11] reported small clinical series of its use and emphasized its many advantages and limited donor morbidity. In situations when a thin and pliable flap is needed, the radial forearm flap has traditionally been the choice flap.…”
Section: Introductionmentioning
confidence: 99%
“…Taylor & Daniel 1 first suggested the medial sural vessels as the basis of a new flap donor site in 1975 and, two decades later, Montegut 2 presented the first clinical cases of the medial sural artery perforator flap. Subsequently, Cavadas 3 and other authors [4][5][6][7][8][9][10][11] reported small clinical series of its use and emphasized its many advantages and limited donor morbidity. In situations when a thin and pliable flap is needed, the radial forearm flap has traditionally been the choice flap.…”
Section: Introductionmentioning
confidence: 99%
“…A study has shown that ABCC1-overexpressing HL-60/ Adr cells are composed of more than 90 % SP cells (Patrawala et al 2005) that are not necessarily associated with increased CSC content. The SP phenotype has been used to identify and isolate normal stem cell populations from a variety of tissues including bone marrow (Goodell 2001), mammary glands (Welm et al 2003), skin (Montanaro et al 2003), liver (Wulf et al 2003), lung (Majka et al 2005), skeletal muscle (Meeson et al 2004), limbs (Umemoto et al 2005), heart (Martin and Dargie 2004) and brain (Kim and Morshead 2003). In addition, overexpression of the ABC transporter is usually related to stem cell markers such as CD133, nestin, CD117 (Adhikari et al 2010), Notch-1 and Nanog (Patrawala et al 2005;Bourguignon et al 2008) as well as Oct-4 .…”
Section: Introductionmentioning
confidence: 99%
“…A review of the English literature about pedicled medial sural perforator flaps for knee defects showed that Umemoto et al performed the flap in the upper third of the lower leg and low portion of the knee in four patients. Kim et al reported on their use of a medial sural perforator island flap for the reconstruction of postburn knee flexion contractures to cover the defect in the posterior knee in 12 patients.…”
Section: Discussionmentioning
confidence: 99%